(untitled) (Fiep Bulletin - online, 2011)
Summary: In virtue of diverse inconclusive results in relation to the intensity and the type of beneficial exercises for the profit of muscular hypertrophy, the present work considered to compare the method prescribed of exercises for the ACMS (2002), with a fiche personalized mounted for the pupil through the theoretical and practical knowledge of the professional of physical education in the attainment of results. The work was carried out with a group of 30 pupils of an Academy of Muriaé-MG, divided in Control Group (CG) and Experimental Group (GE). The work with each integrant one lasted around 3 the 4 months of duration, and the collected data had been analyzed through Test t, using a level of significance of p<0,05 for comparison of the same ones. The results had not most presented significant differences, being that for controlled that were the work, other factors as frequency, feeding, hours of sleep can have intervened with the reply of the results. We conclude that other studies will have to be carried through in order to continue in the evidences or little conclusive search of reply in the more correct form or forms of lapsing.